Turn down of acute aortic syndrome cases during COVID‐19: Results from UK multicentre studies. Issue 1 (10th November 2020) - Roman, Marius; Harky, Amer; Brazier, Andrew; Lim, Kelvin; Gradinariu, George; Oo, Aung; Mariscalco, Giovanni; Lopez‐Marco, Ana
Abstract: Objective: The coronavirus disease 2019 (COVID‐19) pandemic has restructured the healthcare systems, prioritizing resources to treat COVID‐19 patients. The aim of this study was to establish if patients affected by acute aortic syndrome (AAS) had unrestricted access to emergency treatment and evaluate outcome of these patients during the peak of the pandemic. Methods: This is a retrospective analysis of prospectively collected data between March and June 2020 from 19 participating cardiac surgery centers in the United Kingdom. Results: Among 95 patients who presented with an AAS in the participating centers; 85 (89%) underwent surgery, 7 (7%) were turned down for surgery because of their profile of comorbidities, and 3 (3%) died on transfer. Among the patients treated conservatively, three of them (43%) were alive at 30 days. We observed no significant restriction in access to treatment for AAS during the early months of the pandemic. Conclusion: Services for life‐threatening aortic surgery patients were maintained during the COVID‐19 period through patient selection and timing of surgery. The rate of surgical turn‐down was comparable to published figures despite the challenges faced during the COVID‐19 pandemic.